Ten statements to support nurse leaders implement e‐health tools for nursing work in hospitals: A modified Delphi study. Issue 9 (25th February 2021) - Bail, Kasia; Merrick, Eamon; Fox, Amanda; Gibson, Jo; Hind, Alicia; Moss, Cameron; Strickland, Karen; Redley, Bernice
Abstract: Aim: To use expert consensus to develop guidance for nurse leaders implementing e‐health tools to support nursing work in hospitals. Background: Nurse leaders are increasingly required to make decisions about the selection, development, implementation and optimisation of e‐health tools for nursing work in hospitals. Guidance in this rapidly evolving and complex space is limited. Design: A two‐phase modified Delphi study. Methods: Phase one involved in‐depth interviews with five nursing informatics experts. Analysis used the qualitative framework method, informed by the Theoretical Domains Framework (TDF), to develop statements for an anonymous online Delphi scoring survey. This was distributed using snowball sampling methods to Australian nurse informatics leaders and experts. Final analysis involved synthesis of qualitative and quantitative data. The study adheres to the COnsolidated criteria for REporting Qualitative research (COREQ) checklist. Results: Ten guidance statements to support nurse leaders to implement e‐health tools in hospitals were developed from the synthesis of qualitative interview data and 29 experts' responses to the 55‐item Delphi response survey. Conclusion: Implementation of e‐health tools for nursing work is complex in health settings and requires careful examination of multiple factors and interactions between clinicians, tools, service users and the health organisation. This research proposes ten statements to support nurse leaders with decisions about implementing e‐health tools to support nursing work in hospitals. Relevance to clinical practice: The ten statements developed by this research provide a resource to assist policy and practice decisions about e‐tools to ensure they are suited to supporting nursing work. Nurse leaders can use the ten statements for guidance in the selection, development, implementation and optimisation of e‐health tools to ensure suitability and adaptation for nursing work in hospitals.